The Clinical and Functional Characteristics of Chronic Duodenal Insufficiency - Ya. M. Vakhrushev; M. S. Busygina; A. V. Vorobyova; A. M. Farrakhov (SINAPS LLC, 2021)
Purpose: to study the clinical course and features of violations of the motor-evacuation function of the gastrointestinal tract in chronic duodenal insufficiency. Materials and methods. The study included 40 patients with chronic duodenal insufficiency (CDI): 18 (48.2%) women, 22 (51.8%) men, mean age 37.1 ± 13.8 years. The control group consisted of 30 healthy individuals: 10 (33.3%) women, 20 (66.7%) men, mean age 40.5 ± 13.47 years. In the examination of patients, anamnestic and physical data, the results of biochemical, X-ray and endoscopic studies, intracavitary manometry, and electrogastroenterography were used. Parameters reflecting psycho-emotional state and vegetative status were evaluated. Results. In 19 (46.8%) patients with CDI, the pain syndrome occurred after eating, most often localized in the right hypochondrium in 11 (29.0%) and in the epigastric region in 18 (44.9%) patients. Patients with CDF presented some dyspeptic complaints that were not observed in the control group: 22 (57%) noted belching with bitterness, 31 (77.6%) - a feeling of bitterness in the mouth, 21 (53%) - heartburn, flatulence - 25 (53.3%) and mushy stools 28 (71%). In patients with CDI, compared with the control group, there was a decrease in the content of total protein (62.24 ± 0.17 and 72.3 ± 0.21 g/l, p = 0.0002), triglycerides (0.42 ± 0.0021 and 1.5 ± 0.04 mmol/L, p = 0.022), fat-soluble vitamin B12 (188.0 ± 0.21 and 328.6 ± 18.9 pg/ml, p = 0.0048), 25-OH vitamin D (26.87 ± 0.12 and 64.7 ± 1.25 ng/ml, p = 0.018). With CDI, compared with control, a significant increase in gastrin (29.7 [25.7; 32.5] and 19.2 [18.8; 20.1] pmol/L, p = 0.0004) and cortisol (471, 8 ± 1.09 and 365.3 ± 2.6 nmol/L, p = 0.0001). The insulin level was significantly lower than the values of the control group: (2.89 [2.5; 3.0] and 3.8 [2.2; 4.5] μmol/L, p = 0.006). According to the gastroenteromanitor in the postprandial period, impaired propulsive motility in all parts of the digestive tube was established, which proves a decrease in the rhythm coefficient (K-ritm) of the duodenum, jejunum and ileum on an empty stomach by 1.5 times in both phases of the study (p = 0.000). The ratio of intraduodenal pressure to intragastric pressure in chronic heart failure was 1.26 [1.19; 1.32], which is significantly lower than the values in the control group (1.7 [1.0; 2.4], p = 0.0004) and indicates a violation of the closure function of the gatekeeper. Alarm scale RH. Spielberger (adaptation of Yu.L. Khanin) showed an increase in comparison with the control group in the levels of situational (57 [54; 60] and 47.0 [45; 50] points, p = 0.0021) and personal anxiety (25.1 [22.6; 27.4] and 21.9 [19.5; 23.9] points, p = 0.003) in patients with CDI. Conclusion. In connection with the non-manifest course and the absence of specific symptoms of chronic duodenal insufficiency, in the examination of patients for the diagnosis, it is necessary to use, in addition to clinical data, X-ray, endoscopic, manometric and electrophysiological studies.